On the Relation Between Anomalous Clouds and Earthquakes in Italian Land - Guangmeng, Guo (Frontiers in Earth Science, 2022)
In 1997 Russian scientist Morozova found some cloud anomalies possibly related to active fault systems and earthquakes. Now 24 years passed while the correlation between clouds and earthquakes is still controversial, so in this paper we checked systematically the satellite images in Italy from 2010 to 2013. The correlation between earthquakes and cloud anomalies was statistically examined by assuming different various leading time and magnitude. The result showed that when the leading time interval was set to 23≤ΔT≤45 days and the magnitude is bigger than or equal to M4.7, 70% earthquakes were preceded by cloud anomalies. Poisson random test showed that anomaly appearance rate (AAR) and earthquake occurrence rate (EOR) was much higher than those derived in random situation, which means it is nearly impossible to deny the correlation between cloud anomaly and land earthquakes in Italy. Error matrix analysis showed this method provides 75% overall accuracy for the 52 total cases. Analysis also showed that cloud method provides a very high AAR value and similar EOR value compared with ionosphere method and skin temperature method. The physical mechanism of cloud anomaly was likely caused by electric field which linked active fault, atmosphere circuit conduction current and cloud anomaly, and thus provide a reasonable hypothesis of cloud anomaly.